PENGARUH MODAL KERJA TERHADAP LABA PADA PT. SEMEN TONASA (PERSERO) DI KABUPATEN PANGKEP - Qudratul Khaeriah; Nurman Nurman; Uhud Darmawan Natsir (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aimed to determine the influence of working capital on profit at Pt. Semen Tonasa, Pangkep regency. The population in this study were the financial statements of pt semen tonasa from 2016-2020. Data collection was done by using documentation method. The data analysis technique used was simple linear regression analysis using statistical product and service solution (spss). The results of this study indicate that working capital has a positive and significant influence on profits at PT. Semen Tonasa, Pangkep regency. Meaning that, if every working capital used increases, it will increase the company's profit as well.